A Unique Funding Opportunity for Public Health in Texas - Schlenker, Thomas (J Public Health Manag Pract, 2015)
In addition to the Affordable Care Act, states are more frequently turning to Medicaid waivers to achieve the “Triple Aim” goals of improving the experience of care, improving population health, and reducing per capita costs. These demonstration waivers provide opportunities to test innovative ways to finance and deliver care. Texas is currently implementing a waiver known as the Transformation and Quality Improvement Program. Its inclusion of public health agencies is a unique approach to a system typically limited to traditional providers. San Antonio Metropolitan Health District is one public health agency taking advantage of this new funding opportunity to implement 6 new or expanded programs targeting health issues of highest priority in this south Texas region. This article discusses the use of Medicaid waivers and the advantages and challenges of public health agency participation.